2019
DOI: 10.1038/s41398-019-0487-5
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone imbalance may link depression and increased body weight in premenopausal women

Abstract: Accumulating evidence supports a link between depression and being overweight in women. Given previously reported sex differences in fat accumulation and depression prevalence, as well as the likely role of sex hormones in both overweight and mood disorders, we hypothesised that the depression-overweight association may be mediated by sex hormones. To this end, we investigated the association of being overweight with depression, and then considered the role of sex hormones in relation to being overweight and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 81 publications
(92 reference statements)
0
22
2
1
Order By: Relevance
“…However, total estrogen was lower in premenopausal but higher in postmenopausal obese females compared to respective age-matched healthy counterparts [90] with no difference in free estrogen regardless of the menopausal state [91]. Both free and total testosterone levels increased in obese females regardless of the menopause state compared to the healthy counterparts, with an overall higher testosterone level in premenopausal females [91]. In contrast, there was more free estrogen in obese than healthy males [89].…”
Section: Adipokines Lipokines and Endocrine Disruption In Obesitymentioning
confidence: 79%
See 1 more Smart Citation
“…However, total estrogen was lower in premenopausal but higher in postmenopausal obese females compared to respective age-matched healthy counterparts [90] with no difference in free estrogen regardless of the menopausal state [91]. Both free and total testosterone levels increased in obese females regardless of the menopause state compared to the healthy counterparts, with an overall higher testosterone level in premenopausal females [91]. In contrast, there was more free estrogen in obese than healthy males [89].…”
Section: Adipokines Lipokines and Endocrine Disruption In Obesitymentioning
confidence: 79%
“…Consistent with this, lower LH and follicle-stimulating hormone (FSH) levels and lower sex hormone binding globulin (SHBG) were observed in both premenopausal [87] and postmenopausal [88] obese females, and lower total testosterone, FSH, and SHBG were observed in obese males compared to their respective healthy counterparts [89]. However, total estrogen was lower in premenopausal but higher in postmenopausal obese females compared to respective age-matched healthy counterparts [90] with no difference in free estrogen regardless of the menopausal state [91]. Both free and total testosterone levels increased in obese females regardless of the menopause state compared to the healthy counterparts, with an overall higher testosterone level in premenopausal females [91].…”
Section: Adipokines Lipokines and Endocrine Disruption In Obesitymentioning
confidence: 99%
“…Sex differences in anxiety-like behavior partially were affected by aged-related testosterone decline in male rats [ 17 ]. Stanikova et al [ 18 ] suggested that higher free testosterone imbalance may mediate depression in overweight premenopausal women. However, limited efforts have been paid to explore the interactions effects between genetic factors and sex hormone traits for mental traits from sex-specific genetic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in anxiety-like behavior partially were affected by aged-related testosterone decline in male rats [17]. Stanikov et al [18] suggested that higher free testosterone imbalance may mediate depression in overweight premenopausal women. However, limited efforts have been paid to explore the interactions effects between genetic factors and sex hormone levels for mental traits from sex-speci c genetic perspective.…”
Section: Introductionmentioning
confidence: 99%